Do we need a separate banking system? An assessment - Gunnar Lang; Michael Schröder (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Motivated by the current discussion on different separate banking systems, we provide an overview of the different systems, question them and outline their effect on systemic stability and the German banking sector. The results show that the various separate banking systems only play a minor role in reducing and limiting systemic risk. They only marginally contribute to solving conflicts of interest and can even be detrimental to banking business diversification. A separate banking system could, however, facilitate banking supervision by reducing the banking system's complexity. Furthermore, credible threats to not support investment banks with federal resources in times of crisis could lead to a more adequate incentives structure of suppliers of equity and outside capital. More efficient measures to further reduce systemic risk in the financial sector should, however, use different levers, such as additional minimum regulatory capital requirements.
urn:nbn:de:bsz:180-madoc-331742
Keywords: G01; G18; G24; 330; Banking Regulation; Commercial and Investment Banking; Financial Crises